Implikasi Hukum Tindak Lanjut Rekomendasi BPK Terhadap Pertanggungjawaban Perdata Pejabat Pembuat Komitmen dalam Kontrak Pengadaan Barang/Jasa Pemerintah - Rica Lestari; Kurnia Warman; Hengki Andora (Dinasti Research, 2026)
The Commitment Making Officer (PPK) in government procurement activities carries a fundamental dual legal standing: as a state administrative official subject to the public law regime, and simultaneously as a government representative bound in civil law relationships. This duality creates real legal accountability complexities, particularly when the fulfillment of public law obligations—namely the follow-up of the State Audit Board (BPK) recommendations—conflicts with previously agreed contractual obligations. This study aims to analyze the legal implications of BPK audit recommendation follow-up on PPK civil liability and to examine the mechanisms and obstacles in executing court judgments ordering regional governments to pay compensation to goods/services providers. The study employs normative-empirical legal research with a case study approach focusing on Civil Case Decision Number 22/PDT.G.S-2022-PN PDG at the Padang District Court. Results show that: first, the breach of contract arising from contract value deductions without a valid addendum constitutes the liability of the government as a public legal entity not PPK's personal liability based on the faute de service theory; second, execution of court judgments against regional governments faces structural obstacles including prohibition on government asset seizure and the regional budget mechanism, rendering compensation fulfillment entirely dependent on the regional government's good faith.